Latin American Autobiographers, Cosmopolitan Writers: The Textual Ethos of the Exilein Reinaldo Arenas and Sergio Pitol (Letras, 2025)
The lives of Cuban Reinaldo Arenas and Mexican Sergio Pitol, represented literarily in their respective autobiographies Antes que anochezca and Una autobiografía soterrada, project two cosmopolitan Latin American identities whose constitution was determined by exile in large cities (New York, Moscow, Barcelona, etc.). The experiences narrated took place during the Cold War, when the Western/Eastern dichotomy held significant sway due to diverse political and cultural configurations. Within this framework, the historical idea of the “city” and the figure of the “cosmopolitan writer” operate as a mechanism that defines the authors in relation to what Philippe Lejeune called autobiographical identity, that is, the staging of a lyrical self characteristic of the autobiographical genre: the constitution of a textual ethos. In both cases, these are writers who project themselves beyond the borders of their countries of origin. Thus, the objective of this work will be to show how this cosmopolitan identity reflected in the texts of Arenas and Pitol corresponds decisively with the life experiences that both authors had in their exiles, despite the divergent reasons that brought them about: in the first case, exile, in the other, diplomatic functions.
Keywords: Reinaldo Arenas; Sergio Pitol; Autobiography; Cosmopolitanism; City; Exile